Full dark, no stars - King, Stephen, 1947- (New York : Scribner, 2010)
A collection of four new novellas. In the story 1922, a man plunges into the depths of madness when his wife attempts to sell off the family home. A mystery writer, who was beaten and raped while driving home from her book club, plots her revenge in Big Driver. Diagnosed with a deadly cancer, a man makes a deal with the devil in Fair Extension. And in A Good Marriage, a woman discovers her husband's darker side while he is away on a business trip.
Keywords: Retribution -- Fiction; Horror tales, American